(untitled) (Research, Society and Development, 2021)
In this study, we will address the theme related to the Pedagogical Residency Program (PRP), from the question: interface between pedagogical and experiential knowledge? To this end, our research objective is to reflect on the relationship that the Pedagogical Residency Program establishes between the professional training of undergraduate students and the acquisition of experiential knowledge of teaching. Regarding the methodology, the research is of a qualitative nature, supported by bibliographic review, based on the propositions of Nóvoa, Tardif, Charlot and Imbernón, among others, and documentary analysis, having as sources laws, opinions and the Notice CAPES PRP nº 06/2018. Given the above, as a result, the study indicates that the PRP comprises relevant initial training cycles from the direct immersion of residents in the locus of the teaching profession, stimulating the production of experiential knowledge and the experience of dynamics that drive human development and teaching work for the transforming school.